2014
DOI: 10.1111/acem.12384
|View full text |Cite
|
Sign up to set email alerts
|

Council of Emergency Medicine Residency Directors' Standardized Letter of Recommendation: The Program Director's Perspective

Abstract: Objectives: The standardized letter of evaluation (SLOE) was created in 1997 to provide residency program directors (PDs) with a summative evaluation that incorporates normative grading (i.e., comparisons to peers applying to emergency medicine [EM] training). Although the standard letter of recommendation (SLOR) has become increasingly popular and important in decision-making, it has not been studied in the past 12 years. To assess the SLOR's effectiveness and limitations, the perspective of EM PDs was survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
82
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 35 publications
2
82
1
Order By: Relevance
“…The SLOR has also been purported to reduce the grandiosity often seen in narrative letters; nevertheless, subjective and objective analyses have indicated that letter writers continue to consistently select the highest ranks when reviewing student performance. The SLOR thus fails to achieve one of its goals and yields a seemingly homogenous pool of applicants . Multiple studies have shown that when choosing responses in a Likert‐type scale, as is utilized in the SLOR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The SLOR has also been purported to reduce the grandiosity often seen in narrative letters; nevertheless, subjective and objective analyses have indicated that letter writers continue to consistently select the highest ranks when reviewing student performance. The SLOR thus fails to achieve one of its goals and yields a seemingly homogenous pool of applicants . Multiple studies have shown that when choosing responses in a Likert‐type scale, as is utilized in the SLOR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…?” 5 This referred to the incremental increase in number of away rotations students were pursuing. Despite knowledge that strong EM rotation grades and the standardized letter of evaluation (SLOE) carry significant weight6 in an EM residency application, students often buffer their applications with multiple away rotations and apply to dozens of residency programs, irrespective of the overall quality of their candidacy 5. While the clerkship directors declared that more is not necessarily better in respect to rotations and SLOEs, we felt that the addition of EM residency PD attitudes would reinforce the message of the CDEM guide.…”
Section: Introductionmentioning
confidence: 99%
“…Many articles have been widely disseminated despite not being highly cited. For instance, all EM residencies use the “Standardized Letter of Evaluation” (SLOE), as one way of reviewing potential applicants; however, the paper describing its predecessor, the “Standardized Letter of Recommendation (SLOR) and subsequent SLOE papers would not appear on the top 25 cited list in this article 53, 54. This suggests that citation numbers alone do not provide all information regarding the reach of research being performed.…”
Section: Discussionmentioning
confidence: 99%